2005
DOI: 10.1258/002221505775010878
|View full text |Cite
|
Sign up to set email alerts
|

Expression of female sex hormone receptors in human middle-ear cholesteatomas

Abstract: The purpose of this study was to establish the eventual presence of progesterone receptor (PGR) and oestrogen receptor (EGR) in human middle-ear cholesteatoma (MECh) tissues and to compare their expression between male and female patients. An immunohistochemical technique was employed for detection of PGR- and EGR-specific immunoreactivity in MECh samples using formalin-fixed paraffin-embedded tissue sections. The positive results were verified with reverse transcriptase polymerase chain reaction (RT-PCR). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…progesterone receptor and estrogen receptor) differed between male and female patients with cholesteatoma, suggesting that estrogen has an effect on keratinocyte proliferation and differentiation in cholesteatoma. 26 In contrast to the study by Raynov et al, we examined manifestations of bone destruction in chronic otitis media. We focused on ER-α, which is assumed to have a close relationship with bone destruction in chronic otitis media, in contrast to the role of the progesterone receptor.…”
Section: Discussionmentioning
confidence: 99%
“…progesterone receptor and estrogen receptor) differed between male and female patients with cholesteatoma, suggesting that estrogen has an effect on keratinocyte proliferation and differentiation in cholesteatoma. 26 In contrast to the study by Raynov et al, we examined manifestations of bone destruction in chronic otitis media. We focused on ER-α, which is assumed to have a close relationship with bone destruction in chronic otitis media, in contrast to the role of the progesterone receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of sex hormone receptors in human middle ear cholesteatoma, stronger expression of progesterone receptor was found in samples from male patients, while stronger expression of estrogen receptor was found in samples from female patients. It suggests that female sex hormones may stimulate proliferation of middle ear cholesteatoma keratinocytes [67]. Estrogen levels between females and males in different ages may influence the function of the auditory systems, and the details of the mechanism should be studied in the future.…”
Section: Gender Differences In Auditory Functionmentioning
confidence: 99%
“…Although cholesteatoma has been recognized for more than three centuries [20], the nature of this disorder has yet not been fully determined, particularly the factors regulating its progression [28]. Some studies revealed that sex predilection for cholesteatoma might be dependent on the expression of female sex hormone receptors in the middle ear that act as an auditory protectant [43]. It has also been noted that various expression of genes may control pathogenesis of cholesteatomas [3,29,40].…”
Section: Introductionmentioning
confidence: 99%